Improving oxidative stability of echium oil emulsions fabricated by Microfluidics: Effect of ionic gelation and phenolic compounds. (15th October 2017) - Comunian, Talita A.; Ravanfar, Raheleh; de Castro, Inar Alves; Dando, Robin; Favaro-Trindade, Carmen S.; Abbaspourrad, Alireza
Highlights: Encapsulation of echium oil by microfluidic and ionic gelation techniques was feasible. Encapsulated echium oil showed better oxidative stability than the free oil. The echium oil microcapsules were stable under different conditions of stress. Abstract: Echium oil is rich in omega-3 fatty acids, which are important because of their benefits to human health; it is, however, unstable. The objective of this work was the coencapsulation of echium oil and quercetin or sinapic acid by microfluidic and ionic gelation techniques. The treatments were analyzed utilizing optical and scanning electron microscopy, encapsulation yield, particle size, thermogravimetry, Fourier transform infrared spectroscopy, stability under stress conditions, and oil oxidative/phenolic compound stability for 30 days at 40 °C. High encapsulation yield values were obtained (91–97% and 77–90% for the phenolic compounds and oil) and the encapsulated oil was almost seven times more stable than the non-encapsulated oil (0.34 vs 2.42 mg MDA/kg oil for encapsulated and non-encapsulated oil, respectively). Encapsulation was shown to promote oxidative stability, allowing new vehicles for the application of these compounds in food without the use of solvents and high temperature.